Self Concept Mahasiswa UIN Sumatera Utara Medan pada Mata Kuliah Persamaan Diferensial Elementer - Afri, Lisa Dwi; Reflina (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
A positive self concept can provide a strong foundation for students to face academic and social challenges, enhance self motivation, and influence their academic achievements. This research focuses on the affective aspect of students, namely self-concept, which has so far received little attention. The objective of this study is to describe the self concept of students in the Elementary Differential Equations course. The population of this study comprises students enrolled in the 2021 batch of the Elementary Differential Equations course, and a sample of 99 individuals was selected using the Slovin's rule. This research used a quantitative descriptive research method. Data were collected through self-concept questionnaires and interviews. The data were analyzed using descriptive statistics. The results of this study are as follows: (1) The average self concept score of students is 67.3253 out of the ideal score of 96. (2) There are 23 students who have a high self concept with a percentage of 23.3%, 72 students have a moderate self concept with a percentage of 72.7%, and 4 students have a low self-concept with a percentage of 4%. (3) Based on the self concept indicators, the highest average score was obtained in the indicator